Overexpression of miRNA-137 in the brain suppresses seizure activity and neuronal excitability: A new potential therapeutic strategy for epilepsy. (August 2018) - Wang, Wei; Guo, Yi; He, Liang; Chen, Chengzhi; Luo, Jing; Ma, Yuanlin; Li, Jie; Yang, Yong; Yang, Qin; Du, Chao; Zhang, Yanke; Li, Zhonggui; et al.
Abstract: miRNA-137 is an extremely abundant miRNA in the central nervous system and is thought to be closely related to synaptic plasticity. Here, we report a previously unrecognized role of miRNA-137 in epilepsy. The expression of miRNA-137 was decreased both in patients with temporal lobe epilepsy (TLE) and in two different mouse models of epilepsy. Overexpression of miRNA-137 induced by an intrahippocampal injection of a specific agomir prolonged the latency to spontaneous recurrent seizures (SRSs) and reduced seizure severity in a mouse model of pilocarpine-induced epilepsy. Elevated levels of miRNA-137 also prolonged the latency to full kindling and reduced the seizure severity in a mouse model of pentylenetetrazol (PTZ)-kindled epilepsy. Suppression of miRNA-137 levels decreased the latency to the first SRS or the latency to full kindling and increased the seizure severity in both epileptic mouse models. Whole-cell patch-clamp recordings showed that overexpression of miRNA-137 reduced the excitability of pyramidal neurons in the hippocampal CA3a region in a Mg 2+ -free-induced brain slice model of epileptiform activity. This effect may have been achieved by the regulation of the frequency of miniature inhibitory postsynaptic currents (mIPSCs) and presynaptic inhibitory neurotransmitter release. These results suggest that elevated levels of miRNA-137 may exert an antiepileptic effect via a presynaptic neurotransmission mechanism. These data may provide a new potential target and therapeutic strategy for treating epilepsy in the future. Highlights: The expression of miRNA-137 was decreased both in patients with TLE and in two different epileptic mouse models. In vivo miRNA-137 interventions altered the latency and severity of seizures in two mouse models of epilepsy. miRNA-137 might regulate the frequency of mIPSCs by governing the release of presynaptic inhibitory neurotransmitters.